Training and Assistance in Making Product Logos In accordance with the Design Principles for Young Entrepreneurs within Bhinneka PGRI University: Pelatihan dan Pendampingan Pembuatan Logo Produk Sesuai dengan Kaidah Perancangan Bagi Wirausahawan Muda di Lingkungan Universitas Bhinneka PGRI - M. Rizqi Junianto; Ela Rolita Arifianti; Yudha Nesa Suharto (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
A product is a form of innovative work that has market value for the public. Essentially, a product has an identity and distinctive features to stand out among similar products. In line with the needs of the industry and the market, young entrepreneurs continuously enhance their business products. This applies to all aspects, including product logos. The goal of this community service (PkM) is to conduct training and mentoring on the proper design principles for creating product logos for young entrepreneurs in the vicinity of Bhinneka PGRI University. Structured training is expected to enhance skills in designing logos. Intensive mentoring will provide participants with stimuli to better understand the correct methods of design and skillfully use design applications.